Bangladesh investment handbook. - Bangladesh. Board of Investment (Dhaka : Board of Investment, 2002)
Handbook on government initiatives in encouraging foreign investments in Bangladesh.
Keywords: Investments, Foreign -- Government Policy -- Bangladesh -- Handbooks, manuals, etc